Plea Bargaining System, Deffered Prosecution Agreement, dan Judicial Scrutiny sebagai Upaya Mengatasi Overkapasitas Lembaga Pemasyarakatan - Frans, Mardian Putra; Intan Sari, Agustina Indah; Winda, Darisa; Alfret, Alfret; Felix Simeone, Nicholas Gerard (Perspektif Hukum, 2024)
This paper aims to criticize the criminal justice system that is currently unable to overcome the capacity conditions in correctional institutions. This condition is inseparable from the role and contribution of the criminal justice system itself. The justice system in Indonesia is still oriented towards retaliation against perpetrators so that the imposition of punishment by judges results in prison overcapacity. The results of the study found that Legal Concepts such as Deferred Prosecution Agreements as an alternative out-of-court dispute resolution as a form of contante justitie principle because it only involves prosecutors and defendants where judges act as supervisors. In addition, there is the concept of Plea Bargaining System which is a negotiation between the Public Prosecutor and the Defendant who admits his guilt to alleviate the charges and the judicial process can run more efficiently. Judicial Scrutiny plays a role in overseeing the legal process in coercive measures. These three systems should be implemented in the Indonesian legal system to improve and solve the overcrowding of correctional institutions.